2021
DOI: 10.3171/case21451
|View full text |Cite
|
Sign up to set email alerts
|

The surgical resection of dysplastic cerebellar gangliocytoma assisted by intraoperative sonography: illustrative case

Abstract: BACKGROUND Dysplastic gangliocytoma of the cerebellum (Lhermitte-Duclos disease) is an extremely rare, slow-growing hereditary mass lesion that is mainly characterized by both specific neuroradiological features and secondary hydrocephalus. Patients may present with symptoms of cerebellar mass lesion and increased intracranial pressure. As an important part of Cowden syndrome, Lhermitte-Duclos disease in adults is typically marked by PTEN gene mutation. OBSERVATIONS The clinical management of a 31-year-old w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Low rates of postoperative recurrence are associated with complete surgical resection [10] . A previous study reported a 31-year-old patient with LDD who presented with symptoms of increased intracranial cranial pressure and was managed surgically [19] . However, our patient improved symptomatically with antiepileptic medication in the emergency department, and her admission course was uneventful.…”
Section: Discussionmentioning
confidence: 99%
“…Low rates of postoperative recurrence are associated with complete surgical resection [10] . A previous study reported a 31-year-old patient with LDD who presented with symptoms of increased intracranial cranial pressure and was managed surgically [19] . However, our patient improved symptomatically with antiepileptic medication in the emergency department, and her admission course was uneventful.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 , 8 , 15 , 16 ] Remarkably, the lesion often slow growing in nature with unclear boundaries with the adjacent cerebellum making total resection difficult, if not impossible. [ 16 , 17 ] Nevertheless, total resection of the tumor is still considered the most anticipated surgical strategy. [ 16 , 18 ] However, some authors advocate both maximal safe resection as well as preventive C1 laminectomy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 , 18 ] However, some authors advocate both maximal safe resection as well as preventive C1 laminectomy. [ 17 ] Interestingly, intraoperative ultrasound has been used to determine the exact location, specified the lesion resection range, as well as analyzed the blood supply and the venous sinus patency aiding in accurate resection of the lesion. [ 17 ] We attained total resection of the lesion in our case with no neurological deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, subtotal and partial resection of LDD may be acceptable due to its remarkably slow-growing nature. [15] Radiation therapy has been reported as non-effective in avoiding the growth of the lesion. [2,9] Prognosis is favorable and mortality is low, though recurrences may occur due to subtotal resection.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, subtotal and partial resection of LDD may be acceptable due to its remarkably slow-growing nature. [ 15 ] Radiation therapy has been reported as non-effective in avoiding the growth of the lesion. [ 2 , 9 ]…”
Section: Discussionmentioning
confidence: 99%